Preparation method and application of 1500 DEG C-resistant light rigid heat insulation composite material
The mullite/ceramic nanoaerogel composite material prepared by using mullite/sunscreening composite shingles and ceramic nanowater slurry has been solved, and the insulation performance attenuation of existing ceramic-based thermal insulation materials in high temperature environments above 1500°C is achieved, and high-efficiency thermal insulation, low density and low thermal conductivity are achieved. It is suitable for aircraft thermal protection equipment.
Patent Information
- Application Number
- CN202411865218.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-22
AI Technical Summary
The existing ceramic-based thermal insulation materials have attenuated thermal insulation performance in high temperature environments above 1500°C, and have high density and thermal conductivity, making it difficult to meet the needs of aircraft high-temperature protection.
Mullite/sunscreen composite rigid tiles were used as reinforcement bodies, and mullite/ceramic nanoaerogel composites were prepared by RTM vacuum impregnation method. After freeze-drying and high-temperature sintering, a 1500°C-resistant heat-resistant composite material with low thermal conductivity and light weight characteristics was obtained.
A ceramic matrix composite material with high efficiency insulating, low density and low thermal conductivity at high temperatures of 1500℃ is realized, and is suitable for thermal protection equipment for aircraft.
Smart Images

Figure CN119859067A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ultra-high temperature thermal insulation material preparation, and relates to a method for preparing a thermal insulation ceramic-based composite material by a freeze-drying method, and in particular to a method for preparing a 1500°C resistant lightweight rigid thermal insulation composite material and its application. Background Art
[0002] When the new generation of aircraft fly at high Mach numbers in the atmosphere, there is a violent aerodynamic heating effect due to high-speed friction. Therefore, it is necessary to lay thermal insulation materials on the surface of the aircraft to block the transfer of heat inward to ensure the safety and life of the aircraft. When the service temperature of the outer surface of the aircraft is as high as 1500℃, higher requirements are placed on the temperature resistance and thermal insulation performance of the thermal insulation materials.
[0003] At present, the research work on high temperature resistant insulation materials is mainly concentrated in the fields of ceramic fiber insulation materials (ceramic fiber tiles, flexible ceramic fiber felts), nano-ceramic aerogels and their composite materials. The highest temperature tolerance of ceramic fiber insulation materials can reach 1500℃, but due to the large internal pore size, the gas phase thermal conductivity of ceramic fiber insulation materials is high, and its insulation efficiency still needs to be improved. Nano-ceramic aerogels and their composite materials have structural characteristics such as nano-scale pore size distribution, high specific surface area, and high porosity, so they have very low thermal conductivity characteristics and are widely used in the field of ceramic-based insulation. However, the temperature resistance of such materials still needs to be further improved, especially when facing an air environment exceeding 1300℃, the microscopic pore structure of nano-ceramic aerogels and their composite materials will be destroyed, causing their thermal insulation performance to decay or even lose.
[0004] Chinese patent CN 106946579 B discloses a method for preparing a lightweight rigid ceramic fiber thermal insulation tile resistant to 1500°C. The method first prepares a ternary fiber composite rigid ceramic thermal insulation tile, and then introduces SiOC gel to coat the fiber surface to limit the crystallization behavior of the quartz fiber. However, the density of the ceramic tile (0.5-0.8 g / cm 3 ) and room temperature thermal conductivity (0.045~0.055W·m -1 ·K -1) is still relatively high, and there is room for optimization. Chinese patent CN115057713B reports a 1500℃ resistant heat-insulating integrated composite structure ceramic, in which the sandwich structure uses SiC-coated carbon fiber as a suture for suture treatment. This type of structure significantly improves the heat-insulating performance at 1500℃, but its long-term anti-oxidation problem still needs further optimization. Chinese patents CN 111848140B and CN114394612A both use alumina nanowires as basic building units. The "point-to-point" overlap between one-dimensional nanorods and nanowires effectively reduces the sintering effect at high temperatures, so that the temperature resistance of alumina aerogel is increased to 1300℃~1400℃, but when facing higher temperatures, phase change and sintering phenomena will still cause the thermal insulation performance of the material to decay. In addition, the surface of AlOOH nanorods prepared by hydrothermal method is rich in -OH groups, and the viscosity of its aqueous solution is relatively large, and the operability in actual process production still needs to be improved.
[0005] Therefore, it is necessary to provide a ceramic-based thermal insulation material that can withstand high temperatures of 1500°C and has low thermal conductivity based on existing research.
[0006] In summary, it is very necessary to provide a method for preparing a lightweight rigid thermal insulation composite material that is resistant to 1500°C. Summary of the invention
[0007] 1. Technical issues to be resolved
[0008] The technical problem to be solved by the present invention is to develop a ceramic-based thermal insulation material that can withstand a high temperature of 1500°C and has a low thermal conductivity performance to cope with the aerodynamic friction effect between the aircraft and the atmosphere.
[0009] (II) Technical solution
[0010] In order to solve the above technical problems, the present invention provides a method for preparing a 1500°C resistant lightweight rigid thermal insulation composite material, comprising the steps of:
[0011] S1, preparing mullite / sunscreening agent composite rigid tiles;
[0012] S2, preparing ceramic nano water slurry;
[0013] S3, the ceramic nano water slurry described in step S2 is used as an impregnation liquid, and the mullite / sunscreening agent composite rigid tile described in step S1 is used as a reinforcement to prepare a mullite / ceramic nano aerogel composite material, that is, a lightweight rigid thermal insulation composite material resistant to 1500°C is obtained.
[0014] The step S1 of the present invention specifically comprises the steps of:
[0015] S1.1 Mix the sunscreen, high temperature adhesive, organic template and deionized water to obtain a water slurry;
[0016] S1.2 The water slurry is fully mixed with the mullite fiber needle felt by RTM vacuum impregnation method, and the organic matter is gelled to obtain a hydrogel blank;
[0017] S1.3 freeze-drying the hydrogel blank obtained in S1.2 to obtain a composite blank with a porous structure;
[0018] S1.4 The composite blank is subjected to high temperature heat treatment in a muffle furnace to obtain a mullite / sunscreen composite rigid tile.
[0019] As a preferred embodiment of the present invention, the mass ratio of the mullite fiber needle felt, sunscreen, high temperature adhesive, organic template and deionized water is 1: (0.05-1.0): (0.2-1.0): (2.0-5.0): (8-18).
[0020] As a preferred embodiment of the present invention, the treatment temperature of the S1.4 high temperature heat treatment is 800°C to 1200°C, and the treatment time is 1h to 5h.
[0021] As a preferred embodiment of the present invention, the sunscreen is selected from any one of silicon carbide whiskers, titanium dioxide, and potassium titanate whiskers;
[0022] As a preferred embodiment of the present invention, the high temperature adhesive is selected from any one of silicon dioxide, phosphate, and boron nitride;
[0023] As a preferred embodiment of the present invention, the organic template is selected from any one of phenolic acid, agarose and chitosan.
[0024] The step S2 of the present invention specifically comprises the steps of:
[0025] S2.1 Mix acetic acid and deionized water to prepare an acetic acid aqueous solution, then introduce siloxane small molecules and stir until the solution becomes clear and transparent, then introduce chitosan and continue stirring until the chitosan is completely dissolved, finally forming a homogeneous aqueous solution;
[0026] S2.2 The ceramic nanomaterial is mixed with the aqueous solution obtained in step S2.1 by ball milling to obtain the ceramic nano water slurry.
[0027] As a preferred embodiment of the present invention, the raw material ratio in S2 is: ceramic nanomaterial: siloxane small molecule: deionized water: chitosan: acetic acid = 1: (2.0-4.0): (3.0-5.0): (0.04-0.12): (0.01-0.05).
[0028] As a preferred embodiment of the present invention, the ball milling time of the ceramic nanomaterial and the aqueous solution in step S2.2 is 1 to 4 hours.
[0029] As a preferred embodiment of the present invention, the ceramic nanomaterial is selected from any one or more of α-Al2O3 nanosheets, α-Al2O3 nanorods, mullite whiskers, and fully crystallized ceramic microspheres.
[0030] As a preferred embodiment of the present invention, the siloxane small molecule is selected from any one or more of tetramethyl orthosilicate, tetraethyl orthosilicate, methyltriethoxysilane, methyltrimethoxysilane, ethyltriethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, phenyltriethoxysilane, phenyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, octadecyltrimethoxysilane, and octadecyltriethoxysilane.
[0031] The step S3 of the present invention specifically comprises the steps of:
[0032] S3.1 The ceramic nano-water slurry is used as the impregnation liquid, and the mullite / sunscreen composite rigid tile is used as the reinforcement. The ceramic nano-slurry is fully impregnated into the internal pores of the rigid tile through the RTM process, and then the siloxane small molecules are cross-linked and polymerized by heating to form a hydrogel blank;
[0033] S3.2 freeze-drying the hydrogel body obtained in S3.1 to obtain a composite body having a porous structure;
[0034] S3.3 The composite material blank is sintered at high temperature in a muffle furnace to obtain a mullite / ceramic nano-aerogel composite material, that is, a lightweight rigid thermal insulation composite material resistant to 1500°C is obtained.
[0035] As a preferred embodiment of the present invention, the heating temperature in step S3.1 is 50°C to 100°C.
[0036] As a preferred embodiment of the present invention, the sintering temperature in step S3.3 is 1500°C.
[0037] The present invention also provides a lightweight rigid heat-insulating composite material resistant to 1500° C., which is made by the method provided by the present invention.
[0038] The present invention also provides an application of a 1500°C resistant lightweight rigid heat-insulating composite material in the field of heat protection.
[0039] The present invention also provides an application of a lightweight rigid heat-insulating composite material resistant to 1500° C. in thermal protection equipment of an aircraft.
[0040] (III) Beneficial effects
[0041] The above technical solution of the present invention has the following advantages:
[0042] 1. The reinforcement used in the present invention adopts mullite / sunscreening agent composite rigid tile, and the organic template is used to assist the molding control during the preparation process to achieve the uniform dispersion effect of the sunscreening agent on the fiber surface, which has a significant inhibitory property on the radiation heat conduction at a high temperature of 1500°C.
[0043] 2. The matrix material of the present invention is a ceramic nano-aerogel with a stable phase structure. After sintering at a high temperature of 1500°C, the microscopic morphology of the composite material presents a micro-nano pore size distribution, and all components have a stable phase structure. Therefore, the composite material has the characteristics of high-efficiency heat insulation and reusability.
[0044] 3. The mullite / ceramic nano-material aerogel composite material prepared by the present invention has a low density (0.15 g / cm 3 ~0.30g / cm 3 ), low thermal conductivity performance characteristics, the material thickness is selected as 15mm, and the back temperature test is carried out. When the hot surface temperature is 1500℃, the maximum temperature of the cold surface is 420.7℃. It can be seen that the product prepared by the present invention has good low thermal conductivity performance and is suitable for application in thermal protection equipment of aircraft. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 A preparation route map for the mullite / ceramic nanomaterial aerogel composite material of the present invention;
[0046] Figure 2 A microscopic morphology diagram of the mullite / ceramic nanomaterial aerogel composite material provided in Example 2 of the present invention;
[0047] Figure 3 This is a back temperature assessment diagram of the mullite / ceramic nano-material aerogel composite material provided in Example 2 of the present invention (material thickness 15 mm). DETAILED DESCRIPTION
[0048] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0049] Combined with Figure 1 , Figure 1The present invention provides a roadmap for preparing the mullite / ceramic nano-material aerogel composite material. Specifically, a method for preparing a 1500°C resistant lightweight rigid thermal insulation composite material comprises the following steps:
[0050] S1, preparing mullite / sunscreening agent composite rigid tiles;
[0051] S2, preparing ceramic nano water slurry;
[0052] S3, the ceramic nano water slurry described in step S2 is used as an impregnation liquid, and the mullite / sunscreening agent composite rigid tile described in step S1 is used as a reinforcement to prepare a mullite / ceramic nano aerogel composite material, that is, a lightweight rigid thermal insulation composite material resistant to 1500°C is obtained.
[0053] The step S1 of the present invention specifically comprises the steps of:
[0054] S1.1 Mix the sunscreen, high temperature adhesive, organic template and deionized water to obtain a water slurry;
[0055] S1.2 The water slurry is fully mixed with the mullite fiber needle felt by RTM vacuum impregnation method, and the organic matter is gelled to obtain a hydrogel blank;
[0056] S1.3 freeze-drying the hydrogel blank obtained in S1.2 to obtain a composite blank with a porous structure;
[0057] S1.4 The composite blank is subjected to high temperature heat treatment in a muffle furnace to obtain a mullite / sunscreen composite rigid tile.
[0058] Furthermore, the mass ratio of the mullite fiber needle felt, the sunscreen, the high temperature adhesive, the organic template, and the deionized water is 1:(0.05-1.0):(0.2-1.0):(2.0-5.0):(8-18);
[0059] Furthermore, the treatment temperature of the high temperature heat treatment in step S1.4 is 800° C. to 1200° C., and the treatment time is 1 h to 5 h;
[0060] Further, the sunscreen is selected from any one of silicon carbide whiskers, titanium dioxide, and potassium titanate whiskers;
[0061] Further, the high temperature adhesive is selected from any one of silicon dioxide, phosphate, and boron nitride;
[0062] Furthermore, the organic template is selected from any one of phenolic acid, agarose and chitosan.
[0063] The step S2 of the present invention specifically comprises the steps of:
[0064] S2.1 Mix acetic acid and deionized water to prepare an acetic acid aqueous solution, then introduce siloxane small molecules and stir until the solution becomes clear and transparent, then introduce chitosan and continue stirring until the chitosan is completely dissolved, finally forming a homogeneous aqueous solution;
[0065] S2.2 The ceramic nanomaterial is mixed with the aqueous solution obtained in step S2.1 by ball milling to obtain the ceramic nano water slurry.
[0066] Furthermore, the raw material ratio in S2 is: ceramic nanomaterial: siloxane small molecule: deionized water: chitosan: acetic acid = 1: (2.0-4.0): (3.0-5.0): (0.04-0.12): (0.01-0.05);
[0067] Furthermore, the S2.2 ceramic nanomaterial and the aqueous solution are ball-milled for 1 to 4 hours;
[0068] Further, the ceramic nanomaterial is selected from any one or more of α-Al2O3 nanosheets, α-Al2O3 nanorods, mullite whiskers, and fully crystallized ceramic microspheres;
[0069] Further, the siloxane small molecule is selected from any one or more of tetramethyl orthosilicate, tetraethyl orthosilicate, methyltriethoxysilane, methyltrimethoxysilane, ethyltriethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, phenyltriethoxysilane, phenyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, octadecyltrimethoxysilane, and octadecyltriethoxysilane.
[0070] The step S3 of the present invention specifically comprises the steps of:
[0071] S3.1 The ceramic nano-water slurry is used as the impregnation liquid, and the mullite / sunscreen composite rigid tile is used as the reinforcement. The ceramic nano-slurry is fully impregnated into the internal pores of the rigid tile through the RTM process, and then the siloxane small molecules are cross-linked and polymerized by heating to form a hydrogel blank;
[0072] S3.2 freeze-drying the hydrogel body obtained in step S3.1 to obtain a composite body with a porous structure;
[0073] S3.3 The composite material blank is sintered at high temperature in a muffle furnace to obtain a mullite / ceramic nano-aerogel composite material, that is, a lightweight rigid thermal insulation composite material resistant to 1500°C is obtained.
[0074] Furthermore, the heating temperature in step S3.1 is 50°C to 100°C;
[0075] Furthermore, the sintering temperature in step S3.3 is 1500°C.
[0076] Example 1
[0077] This embodiment provides a method for preparing a lightweight rigid thermal insulation composite material resistant to 1500°C. The preparation route is as follows: Figure 1 , including the steps of:
[0078] Step S1:
[0079] S1.1 Silicon carbide whiskers (SiC), silica sol, agarose and deionized water are uniformly mixed in a mass ratio of 1:1:3:15 to obtain a water slurry.
[0080] S1.2 The water slurry obtained in step S1.1 is used as the impregnation liquid, and the mullite fiber needle felt is used as the skeleton. Through the RTM process, the water slurry and the mullite needle felt are fully impregnated and mixed; the temperature sensitive property of agarose is utilized to make the water slurry change from liquid to gel state, and a hydrogel blank is obtained.
[0081] S1.3 The hydrogel blank obtained in step S1.2 is freeze-dried to obtain a composite blank with a porous structure.
[0082] S1.4 The porous composite blank obtained in step S1.3 is subjected to a high temperature heat treatment at 1000° C. in a muffle furnace for 3 hours to obtain a mullite / SiC whisker composite rigid tile with a porous structure.
[0083] Step S2:
[0084] S2.1 Preparation of ceramic nano water slurry: The raw materials and their mass ratio are mullite whisker: tetraethyl orthosilicate: deionized water: chitosan: acetic acid = 1:2:3.2:0.08:0.02. First, prepare a mixed solution of deionized water and acetic acid, then introduce tetraethyl orthosilicate into it, hydrolyze for 2 hours, and after it becomes a clear and transparent solution, introduce chitosan to form a homogeneous solution.
[0085] S2.2 Weigh the mullite whiskers and perform ball milling for 2 h to finally obtain a mullite whisker water slurry.
[0086] Step S3:
[0087] S3.1 The mullite whisker water slurry obtained in step S2 is used as the impregnation liquid, and the porous mullite / SiC whisker composite rigid tile obtained in step S1 is used as the skeleton. The RTM process is again used for full impregnation, and the mixture is heated at 80°C for 10 hours to allow tetraethyl orthosilicate to undergo cross-linking polymerization to form a hydrogel blank.
[0088] S3.2 The hydrogel body obtained in step S3.1 is freeze-dried again to obtain a composite body with a porous structure.
[0089] S3.3 The porous composite body obtained in step S3.2 is placed in a muffle furnace for high-temperature sintering at 1500° C. to obtain a mullite / ceramic nanomaterial aerogel composite material, that is, a lightweight rigid thermal insulation composite material resistant to 1500° C.
[0090] Example 2
[0091] This embodiment provides a method for preparing a lightweight rigid thermal insulation composite material resistant to 1500°C. The preparation route is as follows: Figure 1 , including the steps of:
[0092] Step S1:
[0093] S1.1 Titanium dioxide (TiO2), phosphate, chitosan and deionized water are uniformly mixed in a mass ratio of 1:0.2:4:12 to obtain a water slurry.
[0094] S1.2 The water slurry obtained in step S1.1 is used as the impregnation liquid and the mullite fiber needle felt is used as the skeleton. Through the RTM process, the water slurry and the mullite needle felt are fully impregnated and mixed; the self-entanglement characteristics of the chitosan polymer chain are utilized to form a hydrogel blank supported by hydrogen bonds and physical cross-linking.
[0095] S1.3 The hydrogel blank obtained in step S1.2 is freeze-dried to obtain a composite blank with a porous structure.
[0096] S1.4 The porous composite blank obtained in step S1.3 is subjected to high-temperature heat treatment at 1200°C in a muffle furnace for 2 hours to obtain a mullite / TiO2 composite rigid tile with a porous structure.
[0097] Step S2:
[0098] S2.1 Preparation of ceramic nano water slurry: The raw materials and their mass ratio are α-Al2O3 nanosheets: phenyltriethoxysilane: deionized water: chitosan: acetic acid = 1:3.2:4.8:0.05:0.01. First, prepare a mixed solution of deionized water and acetic acid, then introduce phenyltriethoxysilane into it, hydrolyze for 4 hours, and after it becomes a clear and transparent solution, introduce chitosan to form a homogeneous solution.
[0099] S2.2 Weigh α-Al2O3 nanosheets and perform ball milling for 3 h to finally obtain α-Al2O3 nanosheet water slurry.
[0100] Step S3:
[0101] S3.1 The α-Al2O3 nanosheet water slurry obtained in step S2 is used as the impregnation liquid, and the porous mullite / TiO2 composite rigid tile obtained in step S1 is used as the skeleton, and the RTM process is used again for full impregnation, and heated at 80°C for 10 hours to allow phenyltriethoxysilane to undergo cross-linking polymerization to form a hydrogel blank.
[0102] S3.2 The hydrogel body obtained in step S3.1 is freeze-dried again to obtain a composite body with a porous structure.
[0103] S3.3 The porous composite body obtained in step S3.2 is placed in a muffle furnace for high-temperature sintering at 1500° C. to obtain a mullite / ceramic nano-aerogel composite material, that is, a lightweight rigid thermal insulation composite material resistant to 1500° C.
[0104] Example 3
[0105] This embodiment provides a method for preparing a lightweight rigid thermal insulation composite material resistant to 1500°C. The preparation route is as follows: Figure 1 , including the steps of:
[0106] Step S1:
[0107] S1.1 Potassium titanate whiskers, BN, phenolic acid, and deionized water are uniformly mixed in a mass ratio of 1:0.3:2:8 to obtain a water slurry.
[0108] S1.2 The water slurry obtained in step S1.1 is used as the impregnation liquid and the mullite fiber needle felt is used as the skeleton. The water slurry and the mullite needle felt are fully impregnated and mixed through the RTM process; the characteristic of phenolic resin undergoing gelation transformation under heating conditions is utilized to form a hydrogel blank with organic phenolic resin as the skeleton.
[0109] S1.3 The hydrogel blank obtained in step S1.2 is freeze-dried to obtain a composite blank with a porous structure.
[0110] S1.4 The porous composite blank obtained in step S1.3 is subjected to a high-temperature heat treatment at 900° C. in a muffle furnace for 1 hour to obtain a mullite / potassium titanate whisker composite rigid tile having a porous structure.
[0111] Step S2:
[0112] S2.1 Preparation of ceramic nano-water slurry: raw materials and their mass ratio are, SiO2 ceramic microspheres: vinyltrimethoxysilane: deionized water: chitosan: acetic acid = 1:2.5:4.6:0.06:0.012; first prepare a mixed solution of deionized water and acetic acid, then introduce vinyltrimethoxysilane into it, hydrolyze for 3 hours, and after it becomes a clear and transparent solution, introduce chitosan to form a homogeneous solution.
[0113] S2.2 Weigh SiO2 ceramic microspheres and perform ball milling for 2.5 h to finally obtain SiO2 ceramic microsphere water slurry.
[0114] Step S3:
[0115] S3.1 The SiO2 ceramic microsphere water slurry obtained in step S2 is used as the impregnation liquid, and the porous mullite / potassium titanate whisker composite rigid tile obtained in step S1 is used as the skeleton, and the RTM process is used again for full impregnation, and heated at 95°C for 8h, so that the vinyltrimethoxysilane small molecules undergo cross-linking polymerization to form a hydrogel blank.
[0116] S3.2 The hydrogel body obtained in step S3.1 is freeze-dried again to obtain a composite body with a porous structure.
[0117] S3.3 The porous composite body obtained in step S3.2 is placed in a muffle furnace for high-temperature sintering at 1500°C to obtain a mullite / ceramic nanomaterial aerogel composite material, that is, a lightweight rigid thermal insulation composite material resistant to 1500°C.
[0118] The performance of the 1500°C resistant lightweight rigid thermal insulation composite material provided in the above embodiments was tested, and the microscopic morphology of the 1500°C resistant lightweight rigid thermal insulation composite material provided in Example 2 is shown in FIG. Figure 2 As shown, back temperature test diagram (material thickness 15mm) see Figure 3 .
[0119] Figure 1 It shows the preparation process of lightweight rigid thermal insulation composite material resistant to 1500℃, in which the reinforcement is mullite / shading agent composite rigid tile, and the preparation process uses organic template assisted molding control to achieve the uniform dispersion effect of the shading agent on the fiber surface, which has significant inhibitory properties for radiant heat conduction at high temperature of 1500℃. The matrix material is ceramic nanomaterial aerogel with a stable phase structure. After high temperature sintering at 1500℃, the microscopic morphology of the composite material shows a micro-nano pore size distribution, and all components have a stable phase structure, so the composite material has the characteristics of high efficiency insulation and reusability.
[0120] Figure 2 The microscopic morphology of the composite material is represented by the overlapping of mullite short fibers to form a rigid three-dimensional network skeleton. The porous matrix is attached to the fiber surface and partially fills the pores between the fibers. The whole structure shows obvious porous characteristics, and the pore size has a micro-nano size distribution characteristic. Combined with the complex network porous skeleton characteristics, the composite material has the performance characteristics of light weight and low thermal conductivity.
[0121] Figure 3The thermal insulation performance test results of mullite / ceramic nano-aerogel composite materials are shown in Figure 1. The material thickness is 15 mm. The hot surface temperature is constant at 1500°C, the insulation time is 60 minutes, and the cold surface temperature of the composite material is finally constant between 345.2°C and 420.7°C, indicating that the composite material has high efficiency and long-term thermal insulation performance.
[0122] It should be clear that the various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. For the embodiments of the method, the relevant parts can refer to the partial description of the device embodiment (adopted according to the writing situation). The present invention is not limited to the specific steps described above and shown in the figures. In addition, for the sake of simplicity, a detailed description of known method technologies is omitted here.
[0123] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a lightweight rigid thermal insulation composite material resistant to 1500°C, characterized in that: Includes steps: S1, preparing mullite / sunscreening agent composite rigid tiles; S2, preparing ceramic nano water slurry; S3, the ceramic nano water slurry described in step S2 is used as an impregnation liquid, and the mullite / sunscreening agent composite rigid tile described in step S1 is used as a reinforcement to prepare a mullite / ceramic nano aerogel composite material, that is, a lightweight rigid thermal insulation composite material resistant to 1500°C is obtained.
2. The method according to claim 1, characterized in that: The S1 includes: S1.1 Mix the sunscreen, high temperature adhesive, organic template and deionized water to obtain a water slurry; S1.2 The water slurry is mixed with the mullite fiber needle felt by RTM vacuum impregnation method, and the organic matter is gelled to obtain a hydrogel blank; S1.3 freeze-drying the hydrogel blank obtained in S1.2 to obtain a composite blank with a porous structure; S1.4 The composite blank is subjected to high temperature heat treatment in a muffle furnace to obtain a mullite / sunscreening agent composite rigid tile.
3. The method according to claim 2, characterized in that: The mass ratio of the mullite fiber needle felt, sunscreen, high temperature adhesive, organic template and deionized water is 1: (0.05-1.0): (0.2-1.0): (2.0-5.0): (8-18); The treatment temperature of the high temperature heat treatment in S1.4 is 800°C to 1200°C, and the treatment time is 1h to 5h; The sunscreen is selected from any one of silicon carbide whiskers, titanium dioxide, and potassium titanate whiskers; The high temperature adhesive is selected from any one of silicon dioxide, phosphate, and boron nitride; The organic template is selected from any one of phenolic acid, agarose and chitosan.
4. The method according to claim 1, characterized in that: The S2 includes: S2.1 Mix acetic acid and deionized water to prepare an acetic acid aqueous solution, then introduce siloxane small molecules and stir until the solution becomes clear and transparent, then introduce chitosan and continue stirring until the chitosan is completely dissolved, finally forming a homogeneous aqueous solution; S2.2 The ceramic nanomaterial is ball-milled with the aqueous solution obtained in step S2.1 to obtain the ceramic nano water slurry.
5. The method according to claim 4, characterized in that: The raw material ratio in S2 is: ceramic nanomaterial: siloxane small molecule: deionized water: chitosan: acetic acid = 1: (2.0-4.0): (3.0-5.0): (0.04-0.12): (0.01-0.05); In step S2.2, the ball milling time of the ceramic nanomaterial and the aqueous solution is 1 to 4 hours; The ceramic nanomaterial is selected from any one or more of α-Al2O3 nanosheets, α-Al2O3 nanorods, mullite whiskers, and fully crystallized ceramic microspheres; The siloxane small molecule is selected from any one or more of tetramethyl orthosilicate, tetraethyl orthosilicate, methyltriethoxysilane, methyltrimethoxysilane, ethyltriethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, phenyltriethoxysilane, phenyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, octadecyltrimethoxysilane, and octadecyltriethoxysilane.
6. The method according to claim 1, characterized in that: The S3 includes: S3.1 The ceramic nano-water slurry is used as an impregnation liquid, and the mullite / sunscreening agent composite rigid tile is used as a reinforcement. The RTM process is used to heat and perform a cross-linking polymerization reaction to form a hydrogel blank; S3.2 freeze-drying the hydrogel body obtained in S3.1 to obtain a composite body having a porous structure; S3.3 The composite material blank is sintered at high temperature in a muffle furnace to obtain a mullite / ceramic nano-aerogel composite material, that is, a lightweight rigid thermal insulation composite material resistant to 1500°C is obtained.
7. The method according to claim 6, characterized in that The heating temperature in step S3.1 is 50°C to 100°C; The sintering temperature in step S3.3 is 1500°C.
8. A lightweight rigid thermal insulation composite material resistant to 1500°C, made by the method according to any one of claims 1 to 7.
9. Use of the 1500°C resistant lightweight rigid thermal insulation composite material according to claim 8 in the field of thermal protection.
10. Use of the 1500°C resistant lightweight rigid thermal insulation composite material according to claim 8 in thermal protection equipment of aircraft.
Citation Information
Patent Citations
Preparation method of lightweight rigid ceramic fiber heat insulation tile withstanding 1500℃
CN106946579B
An alumina nanowire aerogel thermal insulation material and its preparation method
CN111848140B
High-temperature-resistant and low-density aluminum oxide nanorod aerogel and preparation method thereof
CN114394612A
A heat-insulating integrated composite ceramic structure resistant to 1500℃ and its preparation method
CN115057713B